Dinamiche insediative nelle campagne dell'Italia tra Tarda Antichità e Alto Medioevo - Barba, Angelo Castrorao (Limina/limites, 2018)
A series of selected contributions about settlement patterns in the Italian countryside between Late Antiquity and the Early Middle Ages, providing a critical overview of the most recent research on the subject.